Glucococorticoid-Induced Death of Pancreatic Beta Cells: An Organized Chaos - Rojas, Joselyn; Chávez-Castillo, Mervin; Chávez-Castillo, Mervin; Cabrera, Mayela; Cabrera, Mayela; Bermúdez, Valmore; Bermúdez, Valmore (JOP. Journal of the Pancreas, 2015)
Glucocorticoids (GC) are renowned for their pleiotropic effects in all organ systems, their ubiquitous use in numerous clinical settings, and the abundant adverse effects they may exert, particularly in the endocrine-metabolic sphere. Although hyperglycemia and insulin resistance are well-defined GC-induced diabetogenic phenomena, an added component of direct injury to pancreatic β cells (PBC) may also participate in this scenario. Indeed, the apoptotic capacity of GC is widely recognized, and PBC do not escape this situation. No unified pathway has been characterized regarding GC-induced cell death; instead, it appears to depend on the specific machinery of each cell type, determining a great heterogeneity in GC-dependent apoptotic mechanisms among different tissues. In PBC, GC can induce the expression or activation of pro-apoptotic proteins (Bax, BAD, p38), repress anti-apoptotic proteins (Bcl-2), deactivate pro-survival mechanisms (cAMP-PKA signaling) and sensitize the cell to death induced by oxidative stress, fatty acids, hyperglycemia and cytokines. Although proliferative pathways (TGF-β, H-ras) are activated simultaneously – and an increase in PBC mass may be observed initially – pro-apoptotic and anti-proliferative mechanisms appear to eventually overcome their pro-survival counterparts, due to their synergic and aggregative action. Key molecules such as p38 and the cAMP-PKA system may be promising therapeutic targets in the prevention of GC-induced cell death. Image: Mechanisms of glucocorticoid-induced death in pancreatic β cells.